How to Develop Learning Materials for English subject used for Economics Students at Universitas Muara Bungo - sufiyandi sufiyandi (Universitas Muara Bungo, 2017)
This research was aimed at finding out how the lecturers develop the learning materials for students at the Economics Faculty of Universitas Muara Bungo in the areas of students’ needs, material stimulatedness, sequencing material, authenticity and supplementary. The research is designed as qualitative study which uses interview as the techniques of the data collection. As it is a structure interview, the instrument of the research was an interview guide supported by an MP3 digital recorder in order to transcribe them later easily. There were three lecturers teaching for the subject teachers referred as teacher A, B, and C that were interviewed concerning with English learning materials. Based on the findings and discussion, the research revealed some interesting areas. Firstly, it was found the lecturers acknowledge the importance of students’ needs prior to developing the learning materials for students of English subject. One of them was the suitability of the materials with the students’ academic achievement. Secondly, the area of study was referred to how to develop the materials that are a stimulus for learning. The use of economic material became consideration. Thirdly, it seemed that the sequencing materials were neglected for several reasons. The other area of study was related to the material authenticity. The materials used for the subject was found to be less in this respect. Finally, the research also found that the supplementary materials for the subject are scarcely found in the class room. Key words: Students’ needs, sequencing, stimulatedness, authenticity, supplementary